2004
DOI: 10.1002/app.20746
|View full text |Cite
|
Sign up to set email alerts
|

Tensile stress relaxation of short‐coir‐fiber‐reinforced natural rubber composites

Abstract: ABSTRACT:The stress relaxation behavior of natural rubber (NR) and its composites reinforced with short coir fibers under tension was analyzed. The rate of stress relaxation was a measure of the increase in the entropy of the compounds: the higher the rate was, the greater the entropy was. At lower strain levels, the relaxation mechanism of NR was independent of strain level. However, the rate of relaxation increased with the strain level. Also, the strain level influenced the rate of stress relaxation conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 21 publications
3
34
0
2
Order By: Relevance
“…6 Geethamma et al studied the relaxation response of short-coir-fiber-reinforced natural rubber and concluded that the strain level, fiber loading, and fiber orientation influence the rate of stress relaxation in the composites. 7 Using composites under life cycle loads is problematic, because the long-time decay of stress should be interpreted and data should be acquired along extensive periods of time which is a tedious process. Therefore, principles such as Boltzmann and time-temperature superposition are invoked to evaluate the long-term viscoelastic behavior of materials by utilizing shortterm data and constructing master curves.…”
Section: Introductionmentioning
confidence: 99%
“…6 Geethamma et al studied the relaxation response of short-coir-fiber-reinforced natural rubber and concluded that the strain level, fiber loading, and fiber orientation influence the rate of stress relaxation in the composites. 7 Using composites under life cycle loads is problematic, because the long-time decay of stress should be interpreted and data should be acquired along extensive periods of time which is a tedious process. Therefore, principles such as Boltzmann and time-temperature superposition are invoked to evaluate the long-term viscoelastic behavior of materials by utilizing shortterm data and constructing master curves.…”
Section: Introductionmentioning
confidence: 99%
“…Bhagawan et al observed an increase in stress relaxation with increase in short jute fiber content in an NBR matrix. 25 The stress relaxation behavior of natural rubber reinforced with coir fibers was studied by Geethamma et al 26 The introduction of particulate fillers in rubber generally results in an increase in relaxation rates. According to the theory of "strain amplification", 27 due to the inextensibility of the filler, the strain in the polymer phase of a filled material is greater than the overall strain.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to thermal crosslinking within the elastomeric phase. [16][17][18] Thermal crosslinking has been confirmed from the swelling studies. The swelling rate decreased by 66% for the aged sample compared to the unaged sample.…”
Section: Resultsmentioning
confidence: 75%